2014
DOI: 10.1039/c4ob00388h
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanistic insights on aryl propargyl ether Claisen rearrangement

Abstract: The mechanism of aryl propargyl ether Claisen rearrangement in gas and solvent phase was investigated using DFT methods. Solvent phase calculations are carried out using N,N-diethylaniline as a solvent in the PCM model. The most favorable pathways involve a [3,3]-sigmatropic reaction followed by proton transfer in the first two steps and then deprotonation or [1,5]-sigmatropic reaction. Finally, cyclization yields benzopyran or benzofuran derivatives. The [3,3]-sigmatropic reaction is the rate-determining step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The thermal cyclization of substituted aryl propargyl ethers by sigmatropic Claisen rearrangements has been described previously as a strategy for the synthesis of chromene derivatives,10 including bioactive natural products 10e,10f. Moreover, recent studies on the rearrangement of aryl propargyl ether to chromenes by theoretical DFT methods corroborate the mechanism proposal 10g…”
Section: Resultsmentioning
confidence: 75%
“…The thermal cyclization of substituted aryl propargyl ethers by sigmatropic Claisen rearrangements has been described previously as a strategy for the synthesis of chromene derivatives,10 including bioactive natural products 10e,10f. Moreover, recent studies on the rearrangement of aryl propargyl ether to chromenes by theoretical DFT methods corroborate the mechanism proposal 10g…”
Section: Resultsmentioning
confidence: 75%
“…[24] Lee and his coworkers made DFT calculations of reaction paths of the aryl propargyl ether rearrangement. [25,26] Rehbein et al reported a kinetic study on an uncatalyzed [3,3]-sigmatropic rearrangement, "Gosteli-Claisen Rearrangement," of 2-alkoxycarbonyl-substituted allyl vinyl ethers. [27] Houk and his coworkers made calculations of transition states of boat and chair conformations of Ireland-Claisen Rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Using 2, 6‐dimethylphenyl propargyl ether and its derivatives, Zsindely and Schmidt reported the rearrangement and suggested its mechanism . Lee and his coworkers made DFT calculations of reaction paths of the aryl propargyl ether rearrangement . Rehbein et al reported a kinetic study on an uncatalyzed [3,3]‐sigmatropic rearrangement, “Gosteli‐Claisen Rearrangement,” of 2‐alkoxycarbonyl‐substituted allyl vinyl ethers .…”
Section: Introductionmentioning
confidence: 99%
“…All of the remaining NMR ( 13 C and HSQC) and MS data were in full agreement with the homocalix[3]arene[1]benzofuran structure of 4 . 9 …”
mentioning
confidence: 99%
“…In the literature, it is proposed that an aryl propargyl Claisen rearrangement usually proceeds through a first [3,3] sigmatropic migration, which leads to an allene intermediate. 9 Due to the entity of the system (C 40 H 44 O 4 ), all calculations were performed at the B3LYP level of theory employing the 6-31+G* basis set ( Supporting Information ). This combination, benchmarked versus several other DFT methods for the aryl propargyl ether Claisen rearrangement, gives the better performance in terms of CPU time and calculated activation energy.…”
mentioning
confidence: 99%